Risk Contingent Credit: A stakeholder engagement to inform project expansion in Kenya - Timu, Anne G.; Shee, Apurba; You, Liangzhi; Girvetz, Evan Hartunian; Ghosh, Aniruddha; Chilambe, Pedro Anglaze (CGIAR System Organization, 2023)
A large proportion of farm households in developing countries face a host of market and production risks that undermine their food security, make their income volatile, and make them hesitant to adopt new technologies or undertake new investments that might increase their long-term productivity and household welfare. Climate-related risks such as floods and droughts remain some of the most pervasive forms of production challenges. Adapting to climate variability and change is essential in safeguarding food security, ensuring economic growth, and advancing climate resilience among smallholder farmers. Recent research has shown that transferring some of the climate-related risks to the insurance market in exchange for a payout can shield the welfare of smallholders from the adverse effects of extreme weather conditions, while agricultural financing can help farmers to acquire and adopt agricultural inputs such as improved seed varieties, fertilizer, pesticides, and herbicides. However, in many developing countries, formal financial markets remain inaccessible to smallholder farmers.